Implementation of a sexual health clinic in an oncology setting: patient and provider perspectives - Andrew G. Matthew; Taylor Incze; Elisa Stragapede; Steven Guirguis; Sarah E. Neil-Sztramko; Dean S. Elterman (BMC Health Services Research)
Abstract Background Sexual dysfunction is prevalent among cancer survivors, significantly impacting patient and partner quality of life. Despite this, sexual health clinics (SHCs) remain rare in cancer centres across Canada. An innovative clinic was developed at Princess Margaret Cancer Centre in Toronto, Canada to address this significant gap in survivorship care. This study examines factors affecting the provision of sexual healthcare and the implementation of a sexual health clinic within a large urban centre. Methods The Quality Implementation Framework was used to explicate patient and provider experience and identify barriers and facilitators to integrating sexual healthcare into routine cancer care workflows. Healthcare providers and patients representing selected cancer types (prostate, cervical, ovarian, testicular, bladder, kidney, and head and neck cancer) participated in semi-structured interviews. Interviews were transcribed and analyzed using the Framework qualitative analysis protocol. Results The analysis identified three organizing domains and ten themes that describe the unique aspects of the sexual healthcare experience and critical factors for sexual health implementation. Both patients and providers described a lack of sexual health support in the oncology setting and emphasized the need for comprehensive and personalized care. Limitations of current care provision included mutual silence between patients and providers due to discomfort in discussing sexual issues, insufficient provider confidence in delivering optimal sexual healthcare, and constraints related to space and time. Key Factors for implementing a sexual health clinic in oncology emphasized the importance of having a dedicated clinic, flexibility in service delivery, proactive patient engagement, and ongoing staff education. Conclusions Findings highlight significant challenges in addressing sexual health in an oncology setting, underscoring the need for specialized sexual health clinics that are integrated with, but distinct from, routine oncology care. This study further emphasizes the need for incorporating sexual healthcare in survivorship programs as well as the necessity of conducting thorough implementation research, involving multiple stakeholders, prior to launching new programs.